Will secular India survive? - Mushirul Hasan. (ed.); Hasan, Mushirul (Gurgaon, Haryana : ImprintOne, 2004)
Contributed articles on secularism, religious fundamentalism, and state machinery in India.
Includes bibliographical references (p. [385]-396).
Keywords: Secularism -- India; Religious fundamentalism -- India